(untitled) (International conference on multidisciplinary science, 2023)
The development of electronic devices is increasing the need for magnetic sensors, which in turn is driving the development of magnetic sensors. In this work, the theory, principle of operation, efficiency and economic value of magnetic sensors based on the Hall effect were considered.